Penerapan Teknik Vokal yang Baik dan Benar dengan Menggunakan Metode Demonstrasi untuk Meningkatkan Kemampuan Bernyanyi Mata Pelajaran Seni Budaya pada Siswa Kelas VII Bilingual di SMPN 4 Mataram - Srininsih, Endang (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
Action Research This class examines "The Application of Good and True Vocal Techniques by Using Demonstration Methods to Increase Singing Ability of Art Subjects Culture on VII Bilingual Grade Students of SMP Negeri 4 Mataram ". Action planning in this study is a learning material and learning scenario, while in the implementation of the action is implementing the learning process in the classroom with the preparation of several instruments, while the cycle action in this research is activity cycle which include planning, execution, observation, and reflection. The results showed that the application of vocal technique is good and correct with using demonstration methods can improve students’ ability to sing. Result data teacher observation in cycle I shows the acquisition of 3.9 and in cycle II 4.6 means an increase 7%. Data on the acquisition of the students at the time of the individual written tests of cycle I obtained an average score of 71, and in cycle II get an average value of 89, means an increase of 18%. Data on acquisition results students at the time of the classical oral test of cycle I get the average value of 71, and in cycle II get the value an average of 87, means an increase of 16%